STUDY CONCERNING THE PRODUCTION OF BIOMASS PROTEIN BY VALORISATION OF BY-PRODUCTS FROM THE DAIRY INDUSTRY ETUDE CONCERNANT L’OBTENTION DE BIOMASSE PROTEIQUE PAR VALORISATION DES SOUS-PRODUITS DE L’INDUSTRIE LAITIERE - LUMINITA GROSU; IRINA-CLAUDIA ALEXA; OANA-IRINA PATRICIU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The development of the food industry ensures the necessary protein for the population and in this perspective the valorisation of by-products from the dairy industry (whey and buttermilk) can be a solution in this direction. Whey is a very important substrate for the biosynthesis of single cell protein by its lactose content which is the main source of fermentable substrate for yeasts. As part of our research, the biomass protein was obtained using whey as source of lactose and other sugars and yeast strains of Candida utilis. The modelling program used is 2nd order system centred with three variables: amount of sugar, amount of nitrogen and quantity of phosphorus. The following parameters have been pursued: biomass content, yield of sugar consumption and protein content. The process conditions are influenced by the addition of different nutrients.